ACTIN-RELATED PROTEIN6 Regulates Female Meiosis by Modulating Meiotic Gene Expression in Arabidopsis . Issue 4 (15th April 2014) - Qin, Yuan; Zhao, Lihua; Skaggs, Megan I.; Andreuzza, Sebastien; Tsukamoto, Tatsuya; Panoli, Aneesh; Wallace, Kirsten N.; Smith, Steven; Siddiqi, Imran; Yang, Zhenbiao; Yadegari, Ramin; Palanivelu, Ravishankar
Abstract : This study shows that ACTIN-RELATED PROTEIN6 regulates female meiosis by determining the spatial and temporal patterns of gene expression required for proper meiosis during ovule development, including expression of the recombinase gene DMC1 . Abstract: In flowering plants, meiocytes develop from subepidermal cells in anthers and ovules. The mechanisms that integrate gene-regulatory processes with meiotic programs during reproductive development remain poorly characterized. Here, we show that Arabidopsis thaliana plants deficient in ACTIN-RELATED PROTEIN6 (ARP6), a subunit of the SWR1 ATP-dependent chromatin-remodeling complex, exhibit defects in prophase I of female meiosis. We found that this meiotic defect is likely due to dysregulated expression of meiotic genes, particularly those involved in meiotic recombination, including DMC1 ( DISRUPTED MEIOTIC cDNA1 ). Analysis of DMC1 expression in arp6 mutant plants indicated that ARP6 inhibits expression of DMC1 in the megasporocyte and surrounding nonsporogeneous ovule cells before meiosis. After cells enter meiosis, however, ARP6 activates DMC1 expression specifically in the megasporocyte even as it continues to inhibit DMC1 expression in the nonsporogenous ovule cells. We further show that deposition of the histone variant H2A.Z, mediated by the SWR1 chromatin-remodeling complex at the DMC1 gene body, requires ARP6. Therefore, ARP6 regulates female meiosis by determining the spatial and temporal patterns of gene expression required for proper meiosis during ovule development.